2018
DOI: 10.1016/j.neuropharm.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

The nicotinic receptor drug sazetidine-A reduces alcohol consumption in mice without affecting concurrent nicotine consumption

Abstract: Alcohol and nicotine addiction are frequently co-morbid. The nicotinic acetylcholine receptors (nAChRs) are critical for both alcohol and nicotine addiction mechanisms, since nAChR drugs that reduce nicotine consumption have been shown to also reduce alcohol consumption. Sazetidine-A, a pre-clinical nAChR drug with agonist and desensitizing effects at α4β2 and α7 nAChRs, has been reported to reduce alcohol consumption and nicotine self-administration in rats when administered at high doses. However, this effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 114 publications
1
23
0
Order By: Relevance
“…We previously showed that systemic sazetidine-A reduced binge DID alcohol consumption in both male and female C57BL/6J mice. 19 Since a major nAChR subtype that is activated and desensitized by sazetidine-A is the α4β2 nAChR, we sought to determine whether the α4 nAChR subunit was important for the actions of sazetidine-A. We tested the effect of systemic sazetidine-A in mice that lack the α 4 nAChR subunit in the DID procedure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that systemic sazetidine-A reduced binge DID alcohol consumption in both male and female C57BL/6J mice. 19 Since a major nAChR subtype that is activated and desensitized by sazetidine-A is the α4β2 nAChR, we sought to determine whether the α4 nAChR subunit was important for the actions of sazetidine-A. We tested the effect of systemic sazetidine-A in mice that lack the α 4 nAChR subunit in the DID procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological manipulation of nAChRs has been shown to reduce alcohol consumption in animal models, as mecamylamine, varenicline and sazetidine-A reduce alcohol consumption in rodents despite their different mechanisms of actions and nAChR subtype targets. [7][8][9]19 Varenicline is best known as a partial agonist at α 4β2 receptors, but in vitro studies show that it is also a partial agonist at α 3* and α 6* receptors and a full agonist at α 7 receptors. 16,[25][26][27] In vitro studies show that sazetidine-A is an agonist at α 4β2, α 3β4*, α 6* and α 7 nAChRs, 15-18 thus sazetidine-A and varenicline act on similar nAChR subtypes but with differing potencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two-bottle choice consumption was performed in a similar manner as our prior work (O'Rourke et al, 2016;Touchette et al, 2018;DeBaker et al, 2019). For each group, the mice were singly housed and presented with one bottle of tap water and one bottle of drug formulation diluted in tap water (either nicotine alone, fruit-flavored nicotine-containing e-liquid, tobacco-flavored nicotine-containing e-liquid, nicotine-free fruit-flavored e-liquid, or nicotine-free tobacco-flavored e-liquid).…”
Section: Voluntary Oral Drug Consumption (2-bottle Choice Tests)mentioning
confidence: 99%